(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this work, we introduce the notions of \(fgb\)-\(I\)-closed sets, \(fgb\)-\(I\)-continuous, \(fgb\)-\(I\)-irresolute, \(fgb\)-\(I\)-open functions and \(fgb\)\(^*\)-\(I\)-open functions in fuzzy ideal topological spaces and investigate some of their characterizations and properties.